HOW SERBIAN RAKIJA DISTILLERS EVALUATE THE QUALITY AND MARKET POSITION OF THEIR SPIRITS - Adžić, Slobodan (Journal of Agricultural Sciences (Belgrade), 2023)
This research aims to answer questions regarding how Serbian distillers evaluate the quality of their products and their chances on the market. The authors also intend to determine the number of market segments for rakija, the Serbian national spirit. As the first known piece of research into the distillers and the economics of rakija production in Serbia, this research will be exploratory in nature. Quantitative research of professional and hobbyist brandy distillers (N = 104) was conducted online in October 2021. Rakija distillers rate the quality of their rakija very highly, while conversely their market situation is rated as being relatively low. They are very enthusiastic about their future market prospects, but with the current approaches to doing business and their outdated approaches to production, their future does not appear bright. It was discovered that the rakija market in Serbia has three segments in relation to the price. The authors concluded that there is no place in the market for distillers who want to offer rakija that is too expensive as a product and, further, of dubious quality. The research findings will be useful to distillers, but also important to agricultural policymakers due to the need to establish stricter standards ensuring rakija quality.
Keywords: rakija; spirits; product quality; market position; segmentation; distillers